Cyberpunk 2077: xoxo (2023) ebook - Sztybor, Bartosz (Cyberpunk 2077: XOXO (2023), 2024)
Only two things can stop a heart from beating: love and death.It’s gang on gang violence as the Maelstroms plan an ambush on the Moxes. The target: corpo cargo worth a heavy sum of cash. But loyalty only goes as far to one’s deepest desires, and one member of the Maelstroms has found something worth sacrificing for. Jaw dropping, eyes popping, pulse racing—he’s never known anyone like her . . . Created in close collaboration with CD Projekt Red, writer Bartosz Sztybor (Cyberpunk 2077: Blackout, Cyberpunk 2077: Edgerunners) and artist Jakub Rebelka (Judas, Origins) ramp up an explosive love story like no other.Collects Cyberpunk 2077: XOXO #1–#4.